Global research trends in biodiversity conservation strategies: A bibliometric analysis - Husamah, H.; Zafira, Aulia Mahdiyatul Dwi; Dalifah, Umrohatul; Permana, Tutut Indria; Rahardjanto, Abdulkadir; Lestari, Nurdiyah (Biological Environment and Pollution, 2025)
This study presents a bibliometric analysis of biodiversity conservation efforts to identify key research trends, themes, and gaps. Using the Scopus database with VOSviewer and RStudio, we analyzed publication trends, co-authorship networks, keyword co-occurrence, and citation patterns. The results reveal a significant surge in publications since 2019, peaking in 2022 and reflecting heightened global focus. The research is highly interdisciplinary, dominated by environmental sciences (35.9%) and agricultural and biological sciences (10.6%). Journals such as Biodiversity and Conservation and Biological Conservation serve as key publication venues. Geographically, Australia, India, and the United States lead in research output, with significant contributions from China and Brazil. Thematic analysis highlights strategic methodologies, ecosystem services, and conservation management as primary research drivers. This study underscores the necessity of international collaboration and interdisciplinary approaches for effective conservation. The insights provide a foundation for future research and offer strategic direction for academics and policymakers to enhance global biodiversity conservation initiatives.